Prevention of post surgical infection in retained and semi retained third molar surgery using two antibiotic prophylaxis regimens with Clindamycin - Silva Infantes, Manuel (2007)
The aim of this study was to compare two antibiotic prophylaxis regimens with Clindamycin in patients under semi-retained third lower molar surgery. Third molar extractions were carried out in healthy patients who complied with the inclusion criteria, in the central clinic surgery service of San Marcos University dentistry faculty. After having performed the exodontia control appointments were programmed during 5 days post – extraction where the infection signs were evaluated through the presence or bleeding or exudates on the surgical bed. This registration was carried out for both groups. The obtained data was analyzed using the Mann-Whitney U test (p <0.05). A significant difference was not found in the proportion of cases infected among the groups. However, the results showed a smaller quantity of patients with infection in the group of the intramuscular via (10%) in relation with the oral via group (15%). It was concluded that there was not a significant difference in the prevention of post – surgical infections of third molars using clindamycin for oral or intramuscular via.